Peningkatan Pemanfaatan Perpustakaan melalui Reward pada Program Literasi Sekolah di Sekolah Dasar Negeri Cibinong 05 - Aisah, Yoelia (Lembaga Yasin AlSys, 2022)
This study aims to determine whether Reward can increase the use of the library at SDN Cibinong 05. Theoretically, it is expected to provide insight and enrich studies on efforts to increase the use of school libraries. The type of research is School Action Research. Data collection techniques by interview, observation, study documentation. Data validation using Triangulation. The data analysis technique used the Miles and Huberman model. The results of the study stated that the average percentage of library utilization in the initial state of 25% was in the low category. Cycle 1 action is to give rewards in the form of certificates of appreciation to students who are most active in using the school library, this action is able to increase the utilization of the school library with a percentage of 41.5% in the medium category, but not in accordance with the established indicators of success. Cycle 2 action by giving rewards in the form of certificates of appreciation and school stationery to the 3 students who were the most active in using the school library, this action was able to increase the utilization of the school library with a percentage of 53% in the medium category and had reached the set indicators. This study concluded that rewards can increase the utilization of the school library at SDN Cibinong 05.